2021
DOI: 10.3390/jcs5120322
|View full text |Cite
|
Sign up to set email alerts
|

Polymerization Shrinkage, Hygroscopic Expansion, Elastic Modulus and Degree of Conversion of Different Composites for Dental Application

Abstract: Objectives: To characterize the mechanical properties of different resin-composites for dental application. Methods: Thirteen universal dentin shade composites (n = 10) from different manufacturers were evaluated (4 Seasons, Grandio, Venus, Amelogen Plus, P90, Z350, Esthet-X, Amaris, Vita-l-escence, Natural-Look, Charisma, Z250 and Opallis). The polymerization shrinkage percentage was calculated using a video-image recording device (ACUVOL—Bisco Dental) and the hygroscopic expansion was measured after thermocy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…All materials were of A2 shade. The composition of tested materials as provided by their respective manufacturers and the available literature [ 25 , 26 , 27 , 28 ] is shown in Table 1 .…”
Section: Methodsmentioning
confidence: 99%
“…All materials were of A2 shade. The composition of tested materials as provided by their respective manufacturers and the available literature [ 25 , 26 , 27 , 28 ] is shown in Table 1 .…”
Section: Methodsmentioning
confidence: 99%
“…Nowadays fissure sealants are widespread and there are several commercial products available for clinicians with a quite different polymerization shrinkage, degree of conversion, and biomechanical properties. These variables related to the composition of the materials could influence the results of the present report [ 49 ]. This concern should be evaluated in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…19 On the other hand, marginal discrepancy and lower bond strength caused by thicker resinous materials could be more evident in complex geometry, such as crowns, due to high polymerization shrinkage of the cement. 20,21 In addition, a thicker cement film exposes more polymeric material to the oral environment, increasing its susceptibility to the degradation. [22][23][24] It was reported that the acceptable cement thickness for dental restorations should be up to 120 μm.…”
Section: Discussionmentioning
confidence: 99%